2014
DOI: 10.1590/1678-4499.259
|View full text |Cite
|
Sign up to set email alerts
|

Is the enhancement produced by priming in cottonseeds maintained during storage?

Abstract: The objective of this study was to evaluate: a) whether the effects of hydropriming and osmopriming in manitol on cottonseed germination are maintained during their storage; b) whether the behavior of the treated seeds -in storage-depends on the type of priming substrate used; c) whether seeds from different harvest years [age] have a similar response. The effects of 16 h of hydropriming and 41 h in mannitol were tested at 18 and 25 °C on the velocity of germination, standard germination and the vigor in cotto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Priming is a pre-sowing treatment that is widely used to promote germination and to improve the quality of seeds under stressed conditions or after ageing from a long period of storage 6 7 . The positive effects of priming treatments, which include halopriming, hydropriming, osmopriming, and thermopriming, among others, on seed performance have been demonstrated in many species 8 . However, these treatments are relatively time-consuming with high labour costs 9 .…”
mentioning
confidence: 99%
“…Priming is a pre-sowing treatment that is widely used to promote germination and to improve the quality of seeds under stressed conditions or after ageing from a long period of storage 6 7 . The positive effects of priming treatments, which include halopriming, hydropriming, osmopriming, and thermopriming, among others, on seed performance have been demonstrated in many species 8 . However, these treatments are relatively time-consuming with high labour costs 9 .…”
mentioning
confidence: 99%
“…These observations were parallel to those already depicted by various workers in different crop such as [21] in cotton; [22] in Brassica juncea; [23] in maize; and [24] in Pearl millet. Toselli and Casenave [25] reported that hydro-priming and osmo-priming increase the germination and vigour index.Similar findings were reported by [26] in sunflower seed and in sorghum seeds by [27]. CD (P = 0.05) L=0.001, T=0.002, L x T=0.003, V x L x T=0.0 IV.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, several chemical products have been used to create seed priming solutions, such as low osmotic potential treatments (osmopriming) from polyethylene glycol (PEG) (Galhaut et al, 2014), NaCl (Bakht et al, 2011), mannitol (Toselli & Casenave, 2014), KNO3 (Singh et al, 2014), KCl (Elouaer & Hannachi, 2012) and CaCl2 (Rehman et al, 2011); nutrients, such as NPK (Al-Mudaris & Jutzi, 1999), Zinc (Prom-U-Thai et al, 2012) and Cu (Begum et al, 2014); and hormones from auxins (GA3) (Heydariyan et al, 2014), brassinolide (Zhang et al, 2007), ethylene (Carvalho et al, 2011c), salicylic acid (Sharafizad et al, 2013), and a wide range of treatments, from acorbic acid (Farooq et al, 2013), selenium (Nawaz et al, 2012), butenolide (Demir et al, 2012), choline (Salama et al, 2011) and chitosan (Mahdavi & Rahimi, 2013) to H2O2 (Santhy et al, 2014), NO (Amooaghaie & Nikzad, 2013) and thiourea (Patade et al, 2012). Curiously, ZnSO4 (osmoconditioning) associated with Trichoderma (biopriming) and application of fungicides (Tivoit and Potent) guaranteed a higher establishment of seedlings and production of rice in the dry season (Zhao et al, 2003), showing a multifaceted approach that involves seed priming.…”
Section: Seed Primingmentioning
confidence: 99%